Efektivitas buku cerita berbasis tradisi rembang untuk peningkatan keterampilan membaca siswa pada pembelajaran bahasa indonesia - Aminah, Aminah; Kanzunnudin, M; Fathurohman, I (Jurnal Pendidikan Dasar, 2023)
The background of this research is because the learning media for reading in grade IV SD is not interesting enough so that children get bored. The teacher's creativity in making or determining learning media does not suit children's interests. Lack of student motivation when participating in learning activities on improving reading skills. The use of learning media is not optimal. The unavailability of teaching materials for Rembang Tradition-Based Storybooks to improve reading skills for Grade IV SD students. The research method is quantitative research in the form of experimental research. Data collection techniques with tests. The research subjects were fourth grade students at SDN Mojokerto, SDN 1 Karangharjo, SDN 2 Karangharjo. Sampling method with purposive sampling. Data analysis using the Paired Sample Test. The results of the analysis of the effectiveness of the pre-test was 21.85 and the post-test was 33.80 with a sig value of 0.000 <0.05, indicating an influence on effectiveness. The conclusion of this study shows that the development of storybooks based on the Rembang tradition is effective for improving students' reading skills in learning Indonesian.